Perdagangan Uang Dengan Uang dan Muamalahnya Dalam Islam - Romi Adetio Setiawan (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
Trading money with money, especially during Eid has become a tradition in Indonesian community, but the provisions regarding the permissibility of this transaction in Islam is still reaping contradictory in society and among scholars, especially no fatwa relating to this case from Indonesian Ulema Council to address this problem, the authors describe some arguments that allow the exchange of money with money, and then cite some opinions from scholars as well as verses and hadith for the consideration in order to find solutions that can be used as a reference in the discussion. Trading money with money is allowed in Islam as long as it is done in cash and no excess levy, taking the wages/exchange services may be carried out but outside the percentage amount of money being exchanged, his wage standards customizable and can be changed according to market supply and demand conditions.Keywords: money exchange, small change, Islamic financial transactions